Charmonium and e+e- pair photoproduction at mid-rapidity in ultra-peripheral Pb-Pb collisions at [Formula: see text] - ALICE Collaboration; Abbas, E; Abelev, B; Adam, J; Adamová, D; Adare, A M; Aggarwal, M M; Aglieri Rinella, G; Agnello, M; Agocs, A G; Agostinelli, A; Ahammed, Z; et al. (The European physical journal. C, Particles and fields, 2013)
The ALICE Collaboration at the LHC has measured the J/ψ and ψ' photoproduction at mid-rapidity in ultra-peripheral Pb-Pb collisions at [Formula: see text]. The charmonium is identified via its leptonic decay for events where the hadronic activity is required to be minimal. The analysis is based on an event sample corresponding to an integrated luminosity of about 23 μb-1. The cross section for coherent and incoherent J/ψ production in the rapidity interval -0.9<y<0.9, are [Formula: see text] and [Formula: see text], respectively. The results are compared to theoretical models for J/ψ production and the coherent cross section is found to be in good agreement with those models incorporating moderate nuclear gluon shadowing at Bjorken-x around 10-3, such as EPS09 parametrization. In addition the cross section for the process γγ→e+e- has been measured and found to be in agreement with models implementing QED at leading order.